2005
DOI: 10.1577/m04-026.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Harvest, Exploitation, Size Selectivity, and Catch Preferences Associated with Winter Yellow Perch Anglers on South Dakota Lakes

Abstract: We evaluated harvest patterns, exploitation, size selectivity, and angler catch preferences associated with winter fisheries for yellow perch Perca flavescens (i.e., ice fishing) on South Dakota lakes. Seasonal trends in the percentage of anglers targeting yellow perch and in yellow perch harvest were apparent in creel surveys on seven lakes; trends varied among lakes. Exploitation of yellow perch was estimated on two lakes through tag-return studies. Nonreporting rates estimated from surrogate postcards varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 44 publications
3
52
0
Order By: Relevance
“…The size distributions of yellow perch caught by anglers changed significantly between 2010 and 2011 (i.e., fewer large fish during 2011) but still fell within ranges observed in other studies (e.g., Isermann et al, 2005). We observed the strongest change in the self-imposed length limit for yellow perch, but it is unknown whether this was from the change in the creel limit or change in the available size structure.…”
Section: Species 2010 2011supporting
confidence: 80%
See 1 more Smart Citation
“…The size distributions of yellow perch caught by anglers changed significantly between 2010 and 2011 (i.e., fewer large fish during 2011) but still fell within ranges observed in other studies (e.g., Isermann et al, 2005). We observed the strongest change in the self-imposed length limit for yellow perch, but it is unknown whether this was from the change in the creel limit or change in the available size structure.…”
Section: Species 2010 2011supporting
confidence: 80%
“…The self-imposed length limits corresponded to sizes observed in other studies that assessed sizes of harvested fish (e.g., Colvin, 2002;Paukert et al, 2002;Isermann et al, 2005;Holley et al, 2009). For example, Isermann et al (2005) found that the mean minimum length of yellow perch harvested by anglers ranged from 21 to 26 cm, depending on the South Dakota lake assessed. In our assessment, the self-imposed length limit ranged from 24 to 33 cm, depending on the year assessed.…”
Section: Species 2010 2011supporting
confidence: 69%
“…Angler size selectivity has been previously documented for yellow perch fisheries (Isermann et al 2005). Isermann et al (2005) documented that the mean minimum total length of yellow perch harvested in a South Dakota lake was 212 mm, indicating anglers set self-imposed minimum length limits without regard to mandated limits.…”
Section: Discussionmentioning
confidence: 87%
“…Isermann et al (2005) documented that the mean minimum total length of yellow perch harvested in a South Dakota lake was 212 mm, indicating anglers set self-imposed minimum length limits without regard to mandated limits. The combination of female-biased SSD with size-selective angler behavior creates the potential for female-biased harvest (Schoenebeck and Brown 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation